The development of a computational model of an osteochondral defect - O'Reilly, Adam (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2016)
Osteochondral defects arise in the knee after structural damage penetrates through the hyaline cartilage and into the underlying subchondral bone. The current surgical options used to treat this condition have limited success in the long term because they fail to successfully regenerate the damaged tissues. While currently not in widespread clinical use, tissue engineering has the potential to reconstruct the native tissue and therefore provide long term relief to the patient. A promising variant of this approach is to insert scaffolds seeded with mesenchymal stem cells (MSCs) into the defect site. The basis of this is that the scaffold will provide the correct mechanical and biological cues to promote the seeded cell population to reconstruct the native tissue. One of the difficulties associated with this treatment option, however, is that the in vivo environment is complex and as a result it is difficult to understand how it will affect cell behaviour within the osteochondral defect. To address this problem, the objective of this thesis was to develop a computational model of MSC differentiation and tissue formation within an osteochondral defect. This model was then used to help improve tissue engineering strategies under development for the treatment of osteochondral defects.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; PhD Trinity College Dublin, 2016